2017
DOI: 10.1021/acs.chemmater.7b01751
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbit[10]uril-Based Smart Supramolecular Organic Frameworks in Selective Isolation of Metal Cations

Abstract: Crystal structure of compound 1 (CIF) Crystal structure of compound 2 (CIF) Crystal structure of compound 3 (CIF) Crystal structure of compound 4 (CIF) Crystal structure of compound 5 (CIF) Crystal structure of compound 6 (CIF) Experimental procedure, Crystal data, PXRD patterns, EDS data (PDF)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 48 publications
(60 reference statements)
0
26
0
Order By: Relevance
“…Close inspection revealed that there are numerous triangular branches in QSF 12 and square branches in QSF 13 that formed regions with ah igh density of portal carbonyl oxygen atoms (Figure 11 c,f). [82] Hydrogen bonding between the solvent water molecules, HCl molecules filling in the branches,and the portal carbonyl oxygen atoms of the Q [10] molecules in the branches also plays an auxiliary role (the water molecules and HCl molecules are omitted for clarity). Generally,asmaller Q[n] with ahigher density of carbonyl oxygen atoms around its two open portals,s uch as Q [5] and Q [6],i sm ore likely to coordinate to metal ions.…”
Section: Qsfsa Ssembled Via Outer-surface Interactions Of Q[n]smentioning
confidence: 99%
“…Close inspection revealed that there are numerous triangular branches in QSF 12 and square branches in QSF 13 that formed regions with ah igh density of portal carbonyl oxygen atoms (Figure 11 c,f). [82] Hydrogen bonding between the solvent water molecules, HCl molecules filling in the branches,and the portal carbonyl oxygen atoms of the Q [10] molecules in the branches also plays an auxiliary role (the water molecules and HCl molecules are omitted for clarity). Generally,asmaller Q[n] with ahigher density of carbonyl oxygen atoms around its two open portals,s uch as Q [5] and Q [6],i sm ore likely to coordinate to metal ions.…”
Section: Qsfsa Ssembled Via Outer-surface Interactions Of Q[n]smentioning
confidence: 99%
“…Similarly, due to the difference in binding affinity, it also exhibited sequence‐selectivity isolation of specific metal cations. Furthermore, the captured metal ions could also be released in HNO 3 medium to recover the metal‐free Q[10]‐based SOF [39] …”
Section: Applications In the Capture And Adsorption Of Hazardous Chemmentioning
confidence: 99%
“…Nowadays, we know that the outer surface interaction of cucurbit[n]urils (Q[n]s), which is attributed to the positive electropotential outer surface of Q[n]s results in the formation of these novel Q[n]-based porous supramolecular frameworks [17]. Our group and others also demonstrated a series of Q[n]-based porous supramolecular frameworks in the absence and presence of different structure directing agents in different mediums [14,[22][23][24][25][26][27][28][29][30][31]. For example, allapally and Tian demonstrated a crystalline form of Q [6] via the outer surface interaction of cucurbit[n]uril, which exhibited high thermal stability, permanent porosity, and the highest specific surface area of any known solid-state forms of Q [6] [22].…”
Section: Introductionmentioning
confidence: 99%
“…Cao and coworkers demonstrated a series of supramolecular compounds constructed from decamethylcucurbit [5]uril (Me 10 Q [5]) and different HPAs or POMs; they found that the Me 10 Q[5]-HPA or POMs-based supramolecular framework exhibited reversible photochromic properties as well as excellent photocatalytic activity toward the degradation of methyl orange and rhodamine B under visible light irradiation [14,25,26]. Recently, we demonstrated a series of simple Q [10]-based supramolecular frameworks in the absence and presence of structure directing agents in aqueous HCl or HNO 3 solutions [27][28][29][30], which not only exhibited sequence selectivity isolation of specific metal cations, thus leading to these architectures being used as metal-selective materials [28], but also exhibited novel adsorption capacities for certain dyes and became novel luminescent materials [29], which could have special selective response to certain volatile compounds [30]. More recently, Fedin and coworkers demonstrated a series of novel supramolecular frameworks based on Q [6] and mono-/polynuclear bismuth(III)-and mercury(II)-ions.…”
Section: Introductionmentioning
confidence: 99%